URGENSI PENGGUNAAN TEKNOLOGI MEDIA DALAM IMPLEMENTASI BIMBINGAN DAN KONSELING DI SEKOLAH - A. Said Hasan Basri (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2018)
BK teacher as a counselor figure who is a source of help for counselee problems, as well as student self-development media as counselees. Always be demanded by professionals and update their knowledge and competence to be able to carry out their duties properly, and the goals of guidance and counseling are achieved. But unfortunately the real conditions in the field, there are still many BK teachers who have not reinforced these aspects. So it is less able to balance its performance with the development of science and technology. Whereas technology as a result of knowledge becomes a very important media in the implementation of guidance and counseling services. The purpose of this study is to describe the various forms of media technology used by BK teachers, and what technologies are most commonly used, as well as what factors are obstacles and supporters of the use of media technology in the implementation of guidance and counseling in schools. The four subjects involved were chosen purposively, namely two counselors and two students. The data collection techniques using interviews, observation and documentation. As a result, the media used in guidance and counseling services include human-based media, print technology-based media, visual-based media, audio-visual media and computer-based media. While the use of technology media in guidance and counseling has not been maximized, it only uses three types of hardware and one type of software. The hardware used is only mobile phones, laptops and LCD projectors. Whereas the BK program application in the form of software only uses the sociometry application program. And inhibiting factors in the use of media technology guidance and counseling, among other things in the form of internal and external factors. The internal factor is the capacity of the BK teacher. Where the BK teacher's competence in the development of media technology is still lacking. While external factors that become obstacles are the limited number of BK personnel (unbalanced ratio between BK personnel and the number of students), then the existing facilities and infrastructure facilities still do not meet the ideal BK service standards. Then the lack of good system support from the school, such as the absence of efforts to increase the ability of BK personnel by training their ability in mastering technology.